2003
DOI: 10.5194/hess-7-525-2003
|View full text |Cite
|
Sign up to set email alerts
|

Modelling long-term changes in stream water and soil chemistry in catchments with contrasting vulnerability to acidification (Lysina and Pluhuv Bor, Czech Republic)

Abstract: In two Czech catchments covered by Norway spruce forests, the MAGIC model was used to simulate annual stream water and soil chemistry for the period 18512030. These two sites represent geochemical end-members of ecosystem sensitivity to acidification (acid-sensitive granitic Lysina catchment vs. acid-resistant serpentinitic Pluhuv Bor catchment). Although the total deposition of sulphur to the catchments declined by 75% between 1990 and 2002, the recovery of stream water pH was relatively small over this perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 22 publications
2
71
0
Order By: Relevance
“…13 Under a thin (a few cm) organic layer, the soil shows clayey texture of grey in color down to a certain depth (~50 cm), and below this depth fragile dark green fragments appeared as a predominant phase. In contrast, the soils from Lysina and Nacetin showed highest value of It is now speculated that there might be potential factors influencing variability of 40 K isotope ratio in soil.…”
Section: Potassium and Radio-potassium ( 40 K) In Soilmentioning
confidence: 99%
“…13 Under a thin (a few cm) organic layer, the soil shows clayey texture of grey in color down to a certain depth (~50 cm), and below this depth fragile dark green fragments appeared as a predominant phase. In contrast, the soils from Lysina and Nacetin showed highest value of It is now speculated that there might be potential factors influencing variability of 40 K isotope ratio in soil.…”
Section: Potassium and Radio-potassium ( 40 K) In Soilmentioning
confidence: 99%
“…Bulk precipitation and throughfall have been collected at several sites ( Fig. 1) monthly since the beginning of 1990s [10]. Stream water discharge have been monitored continuously using V-notch weirs and mechanical water level recorders since September 1989 at Lysina and since November 1991 at Pluhův Bor [21].…”
Section: Methodsmentioning
confidence: 99%
“…In the early 1990s, runoff from Lysina was acidic and high in Al concentrations [2]. Long-term changes in Al concentrations have been simulated by the MAGIC model in both catchments [10]. A combination of a MAGIC model with a model that predicts short-term transient changes in hydrochemistry during hydrologic events (pBDM) showed that Al mobilization was highly variable at Lysina due to historic changes in acidic inputs [16].…”
Section: Site Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large reductions in S and N inputs in the 1980s and 1990s have resulted in significant reversal of acidification in some of these fresh waters . Dynamic models have been successfully applied to many catchments in the region (Majer et al, 2003;Hruška and Krám, 2003;Kopáček et al, 2004a) and have proven to be robust in predicting changes in soil and water chemistry in response to the decreased deposition. Future predictions based on expected atmospheric emission reductions required under European Union agreements (Gothenburg Protocol -UN-ECE, 1999), however, show that recovery of these ecosystems is complicated by continued leaching of sulphate (SO 4 ), and in some cases nitrate (NO 3 ), from soils exposed to long-term deposition of these compounds (Kopáček et al, 2002;Hruška et al, 2002).…”
Section: Introductionmentioning
confidence: 99%